Fighting through language? Neologisms in the Instagram hashtag #ResetIndonesia: A morphological study - Sevi Rahayu; Muhammad Yunus Anis (Universitas Galuh, 2026)
This study examines neologisms in digital resistance discourse in Instagram posts tagged #ResetIndonesia. Neologisms not only reflect linguistic innovation, but also represent critical attitudes, collective identity, and resistance to power. This study aims to identify the process of neologism formation and analyze its social and discursive functions in digital resistance. The research uses a descriptive qualitative approach through observation and documentation of Instagram posts. Data analysis refers to Yule's word formation theory and Androutsopoulos' digital discourse framework. The results show 45 neologisms formed through seven morphological processes, with derivation as the dominant process, particularly through the affixation of pe-...-an, ke-...-an, and meN-. Functionally, neologisms play a role in ideological evaluation, delegitimization of power, mobilization of collective action, and construction of collective identity. This study enriches morphological studies by presenting an empirical mapping of Indonesian neologisms in the context of digital activism, as well as deepening the study of digital discourse by demonstrating the role of morphological forms as discursive strategies of resistance on social media.